Introduction to podcasting - Murphy, Daniel; Safari eBooks ([S.l.] : Total Training, 2009)
"In today's Digital Age anyone with an Internet connection, a computer and some basic audio equipment can produce a Podcast and make it available to the worldwide online community. Podcasts are used to market businesses, educate and train others or simply just for fun. Join Daniel Murphy as he shows the basic elements that are required to produce a Podcast, including microphones, audio recording/editing software, mixers and soundcards. With step-by-step explanations and plenty of examples, this tutorial will help you produce and publicize your own professional sounding Podcasts"--Resource description page.
Title from resource description page (viewed Oct. 5, 2009).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Electronic reproduction.
Keywords: Podcasting; Webcasting; Electronic books